PEMANFAATAN ASAP CAIR ARANG TEMPURUNG SEBAGAI BAHAN PENGAWET PADA BAKSO IKAN TUNA - Korah, Alfi R. M.; Assa, Jan Rudolf; Koapaha, Teltje (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
ABSTRACTThe research objective was to determine the effect of coconut shell charcoal liquid smoke on the shelf-life of fish meatballs. The design used was Factorial Completely Randomized Design, which consisted of 2 factors: A treatment of liquid smoke concentration 0%, 5%, 10%, and factor B treatment of immersion 30 and 45 minutes long, with three repetitions. The results showed that with the concentration of liquid smoke 0% tuna meatballs can last only one day at room temperature with the results of already whitish slimy appearance, fishy flavour, and the texture is still chewy. Fish meatballs with 10% liquid smoke concentration combine with 45 minutes soaking time can last up to 5 days at room temperature with the results of already slimy, brownish, flavorful appearance typical of fish with a chewy texture.Keywords: Liquid smoke, tuna fish meatballs, shelf-life